Phaco-endocycloplasty: A novel technique for management of ring iridociliary cyst presenting as acute angle closure - Vanita Pathak-Ray; Iqbal Ike K Ahmed (Oman Journal of Ophthalmology, 2016)
Iridociliary cysts of pigment epithelium are rare, ring cysts being rarer still, and usually benign in their clinical course. Presented here is a case of ring iridociliary cyst that resulted in secondary synechial angle closure with an acutely elevated intraocular pressure, refractory to medical treatment. Primary endocycloplasty and cataract extraction with implant were used successfully to manage the case.